2008
DOI: 10.1007/s00421-008-0894-4
|View full text |Cite
|
Sign up to set email alerts
|

Countering postural posteffects following prolonged exposure to whole-body vibration: a sensorimotor treatment

Abstract: Postural stability of bulldozer operators after a day of work is investigated. When operators are no longer exposed to whole-body vibration (WBV) generated by their vehicle, their sensorimotor coordination and body representation remain altered. A sensorimotor treatment based on a set of customized voluntary movements is tested to counter and prevent potential post-work accidents due to prolonged exposure to WBV. This treatment includes muscle stretching, joint rotations, and plantar pressures, all known to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…In fact previous studies have demonstrated an immediate suppression of reflex activity in response to acute WBV (Martin, Roll, & Gauthier, 1986) followed by recovery within 1-30 min (Armstrong et al, 2008;Kipp, Johnson, Doeringer, & Hoffman, 2011;Roll, Martin, Gauthier, & Mussa, 1980). Additionally, when exposed to longer period of vibration the responsiveness of the sensor motor system was shown to be ''recalibrated'' with voluntary movements of the muscles nearly immediately (Oullier et al, 2009). Although the current studies recovery period of 10-20 min falls within this reported period the current study measured a more global neuromuscular response similar to that of Oullier and colleagues (Oullier et al, 2009).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In fact previous studies have demonstrated an immediate suppression of reflex activity in response to acute WBV (Martin, Roll, & Gauthier, 1986) followed by recovery within 1-30 min (Armstrong et al, 2008;Kipp, Johnson, Doeringer, & Hoffman, 2011;Roll, Martin, Gauthier, & Mussa, 1980). Additionally, when exposed to longer period of vibration the responsiveness of the sensor motor system was shown to be ''recalibrated'' with voluntary movements of the muscles nearly immediately (Oullier et al, 2009). Although the current studies recovery period of 10-20 min falls within this reported period the current study measured a more global neuromuscular response similar to that of Oullier and colleagues (Oullier et al, 2009).…”
Section: Discussionmentioning
confidence: 50%
“…Additionally, when exposed to longer period of vibration the responsiveness of the sensor motor system was shown to be ''recalibrated'' with voluntary movements of the muscles nearly immediately (Oullier et al, 2009). Although the current studies recovery period of 10-20 min falls within this reported period the current study measured a more global neuromuscular response similar to that of Oullier and colleagues (Oullier et al, 2009). However, unlike previous investigations the present study assessed postural control in altered sensory environments further necessitating the involvement of the somatosensory systems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One might therefore expect that vibration, as an interfering stimulus, should lead to an immediate deterioration of balance (Oullier et al 2008). It seems, however, that the mode of vibration application, as well as people's age need to be considered.…”
Section: Balance and The Risk Of Fallsmentioning
confidence: 96%
“…A sensorimotor treatment based on a set of customized voluntary movements is tested to counter and prevent potential post-work accidents due to prolonged exposure to whole body vibration, [9]. Exposure to whole body vibrations predicts subsequent disability pension retirement continue reduction of whole-body-vibrations may reduce the number of new cases of disability pension, [2].…”
Section: Introductionmentioning
confidence: 99%